Sexual and Gender Minority College Student Retention: The Unique Effects of Mental Health and Campus Environment on the Potential for Dropout - Nicholas W. McAfee; Julie A. Schumacher; Chris A. Kelly (The Ohio State University Libraries, 2023)
Background: While limited data has been collected, some findings show that sexual and gender minority (SGM) students are at higher risk for dropping out of college than their peers. Research on issues such as campus connectedness and mental health among this population indicates both may affect retention.  Aim: This study examined how mental health and perceptions of campus connectedness may mediate the relationship between SGM identification and intentions to drop out of college. Methods: Survey data collected from 1,793 randomly selected students across eight different public universities in Mississippi were used to conduct a parallel mediation analysis.   Results: Mediation analyses indicated that there was a significant direct effect of SGM identity on intentions to drop out, and that both mediators had a significant indirect effect. Psychiatric symptoms had a relatively larger indirect effect than campus connectedness. Conclusions: These results contribute to the limited quantitative literature on SGM student retention, supporting previous work indicating these students are at higher risk of attrition. The results suggest that student retention may be bolstered if access to SGM-competent mental health services is provided. Additionally, campuses should continue to support SGM-friendly policies and create inclusive spaces as a protective resource for students.